Perencanaan Cold Storage Untuk Pengawetan Daging Sapi PT. Kepurun Pawana Indonesia - Roswati Nurhasanah; Aris Sudarmadi (Sekolah Tinggi Teknik - PLN, 2013)
This study describes the analytical calculation of cold storage for preservation planning of beef in PT. Kepurun Pawana Indonesia (PT. KPI). Planning this cold storage will be addressed to the PT. KPI in Yogyakarta that one of his business is cattle farm. Because cattle results from this farm will be sold in the form of fresh beef. Therefore, these companies require cold storage for the storage of beef. Cold storage is intended to keep the quality of beef stays fresh, quality is maintained and not easily damaged or rotten. Cold storage planning begins by calculating the heat load of the product itself, followed by the calculation of the human load, load infiltration, load lighting and lighting loads. After that we can survey the price of machines such as evaporators, condensers, compressors and other equipment from the calculation that writers get. By designing the cold storage, is expected to help and solve the problem of PT. KPI itself in preserving beef before sale to consumers. Meat sales volume instability problems caused by market conditions can be overcome.